PATHOLOGICAL STUDY ON LARYNGOTRACHEITIS IN LAYERS - Al—Hyali , H.M.I.; Al—Job0ury , K.H.Z.; Ismail, A.O. (The Iraqi Journal of Veterinary Medicine, 2021)
A clinical conditions resembling infectious laryngotracheitis were diagnosed amongst 20,000 , 18,000 , 16,000 and 17,500 respectively, 28-30 weeks old, ISA brown layers.The hens had nasal discharges, moist rales, coughing and gasping. Hemorrhagic mucous was ejected during sneezing, lacrirnation, conjunctivitis with facial swelling with eyes partially or completely" closed.Postmortum examination of dead and affected hens revealed hemorrhagic tracheitis with thin pseudomembrane formation. The larynx, congested with petechia on mucous membrane, Infraorbital sinus contained clear thick ﬂuid.Histopathological examination of trachea showed hypertrophy, of epithelial pseudostratiﬁcation of the mucosal cell surface, extensive hemorrhages and desquamative necrotizing tracheitis withmononuclear cells inﬁltration. Multinucleated gaint cells in theciliated epithelium containing round, oval shaped intranuclear Ainclusion bodies. The lamina propiia shows edema, marked‘ congestion with lymphocytic inﬁltration.A presumptive diagnosis of laryngotracheitis was made.